Caracterização geotécnica de solos na região metropolitana do Cariri/CE para uso em pavimentação - Mascarenhas, Ilania Maria Nascimento (2016)
This work seeks to survey and characterization of the types of soil in the Metropolitan Region of Cariri (RMC), located in the southern state of Ceará, for paving purposes. Therefore, in a first stage, were obtained geomorphological data of the region and later created thematic maps of biophysical characteristics such as climate, topography, hydrography, vegetation, geology, soil science, beyond the paved road network of the study area. In the second stage of the research, soils were collected which were classified by the American classification of AASHTO (American Association of State Highway and Transportation Officials) and Brazilian MCT classification (Miniature, Compacted, Tropical). The collected soils were submitted to chemical, physical and mechanical tests that were known their technological properties. According to the classification of AASHTO was revealed that soil behavior forecast is bad for use in flooring. However, the results of the CBR ranged from 24% to 40%, contradicting what one would expect the use of the samples after the American soil classification. MCT classification also not adapted to the soils which stood in a transition zone between lateritic and non lateritic soils. When observing the other tests, the soil showed typical characteristics of lateritic soils with behavior such as low activity of the clay fraction and the presence of iron and aluminum oxides. The Resilience Module results corroborate the expectation of soils with good strength and indicated that the composite model for these samples was not what best represented the materials. Finally, they were scaled several floors based on the soils and all showed good support for multiple traffic requests. It is concluded that the MRC soils need to be better characterized to be applied in pavements.